2017
DOI: 10.3389/fncel.2016.00300
|View full text |Cite
|
Sign up to set email alerts
|

Histamine Increases Neuronal Excitability and Sensitivity of the Lateral Vestibular Nucleus and Promotes Motor Behaviors via HCN Channel Coupled to H2 Receptor

Abstract: Histamine and histamine receptors in the central nervous system actively participate in the modulation of motor control. In clinic, histamine-related agents have traditionally been used to treat vestibular disorders. Immunohistochemical studies have revealed a distribution of histaminergic afferents in the brainstem vestibular nuclei, including the lateral vestibular nucleus (LVN), which is critical for adjustment of muscle tone and vestibular reflexes. However, the mechanisms underlying the effect of histamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Lentivirus (LV)-Crf-RNAi treatment significantly shortened stride lengths (n = 10; left stride length: p < 0.001; right stride length: p < 0.001) and lengthened stride width (n = 10, p < 0.05) ( Figure 1D). We also applied rota-rod and balance beam tests [19][20][21] to examine the effect of downregulation of Crf mRNA in the IO on motor coordination and balance. Rats treated with LV-Crf-RNAi displayed a remarkable decrease in the time spent on the accelerating rota-rod (n = 10, p < 0.001) ( Figure 1E) and a prolonged time traversing the balance beam (n = 11, p < 0.001) ( Figure 1F).…”
Section: Downregulation Of Crf Mrna In the Inferior Olive Induces Atamentioning
confidence: 99%
See 3 more Smart Citations
“…Lentivirus (LV)-Crf-RNAi treatment significantly shortened stride lengths (n = 10; left stride length: p < 0.001; right stride length: p < 0.001) and lengthened stride width (n = 10, p < 0.05) ( Figure 1D). We also applied rota-rod and balance beam tests [19][20][21] to examine the effect of downregulation of Crf mRNA in the IO on motor coordination and balance. Rats treated with LV-Crf-RNAi displayed a remarkable decrease in the time spent on the accelerating rota-rod (n = 10, p < 0.001) ( Figure 1E) and a prolonged time traversing the balance beam (n = 11, p < 0.001) ( Figure 1F).…”
Section: Downregulation Of Crf Mrna In the Inferior Olive Induces Atamentioning
confidence: 99%
“…All behavioral trainings/tests started at the same time (10:00 a.m.) each day. In order to achieve a stable motor performance on the rota-rod and balance beam, each animal was trained daily for at least 10 trials for 3 to 5 consecutive days before test as we previously reported [19][20][21].…”
Section: Immunofluorescencementioning
confidence: 99%
See 2 more Smart Citations
“…[32] The HCN isoforms at axon terminals have been shown to regulate vesicle release, such as regulating gamma-Aminobutyric acid(GABA) release pre-synaptically [33] and glutamate release through voltage-gated T-type calcium (Ca[V]3.2) channels. [34] The coupling of HCN channels to other proteins, such as histamine H2 receptors [35] and Atype potassium channels, has also been shown to regulate neuronal excitability. [36] In summary, I(h) in the soma and proximal dendrites functions to depolarize and stabilize the resting membrane potential, and in distal dendrites, it decreases dendritic integration and limits dendritic calcium spikes.…”
Section: Neuronal Distribution Of Hcn Channelsmentioning
confidence: 99%